Perceived Stress and Clinical Insomnia in Primary Care: Associations with Lifestyle and Medication Use - De las Cuevas C; Segovia Díaz M (Patient Preference and Adherence)
Carlos De las Cuevas,1 María Segovia Díaz2 1Department of Internal Medicine, Dermatology and Psychiatry and Instituto Universitario de Neurociencia (IUNE), University of La Laguna, La Laguna, Canary Islands, Spain; 2School of Medicine of the University of La Laguna, San Cristóbal de La Laguna, Santa Cruz de Tenerife, SpainCorrespondence: Carlos De las Cuevas, Department of Internal Medicine, Dermatology and Psychiatry, Faculty of Medicine of the University of La Laguna, San Cristóbal de La Laguna, Canary Islands, Spain, Email ccuevas@ull.edu.esPurpose: Insomnia and perceived stress are among the most prevalent health concerns in primary care, yet their complex relationship remains underexplored. This study examines the association between perceived stress and insomnia severity, while considering the potential moderating or mediating effects of lifestyle factors and medication use.Methods: A cross-sectional study was conducted with 300 consecutive primary care patients who completed validated questionnaires assessing insomnia severity (Insomnia Severity Index, ISI) and perceived stress (Perceived Stress Scale, PSS). Logistic regression models were employed to identify predictors of clinical insomnia and explore key relationships.Results: A moderate but statistically significant correlation (r = 0.460, p < 0.001) was observed between perceived stress and insomnia severity. In logistic regression analysis, higher perceived stress scores (OR = 1.134, p < 0.001) and hypnotic medication use (OR = 3.220, p < 0.001) were significant predictors of clinical insomnia. Interestingly, alcohol consumption was unexpectedly associated with insomnia (OR = 0.551, p = 0.048), warranting further exploration. No significant associations were found for caffeine intake, tobacco use, or demographic variables. The model explained 33% of the variance in insomnia (Nagelkerke R² = 0.328).Conclusion: These findings highlight the significant role of perceived stress in insomnia severity and underscore the complex interplay between pharmacological interventions and sleep disturbances. While hypnotic medications are commonly used, their long-term impact and potential dependence require careful consideration. Integrating stress-reduction strategies into primary care may improve insomnia management while reducing reliance on pharmacological treatments. Future research should employ longitudinal designs to clarify causality and further explore additional factors influencing sleep disturbances.Plain Language Summary: Why was this study conducted?: Stress and insomnia are common in primary care, but their relationship remains unclear. This study explores how perceived stress influences insomnia severity and whether factors like medication use, alcohol, or caffeine affect this link.What did the study find?: Higher stress levels significantly increased the risk of clinical insomnia; sleep medication use tripled the likelihood of insomnia, suggesting possible dependence; alcohol consumption was unexpectedly linked to lower insomnia risk, though this requires further investigation; and, caffeine and tobacco had no significant impact on insomnia.What do these results mean?: Managing stress is key to improving sleep. While sleep medications are widely used, they may not always be the best solution. Healthcare providers should prioritize stress-reduction strategies and non-pharmacological insomnia treatments to improve sleep quality in primary care patients.Keywords: insomnia, perceived stress, primary care, sleep medication, lifestyle factors, mental health